The Aristotelian Athenaion Politeia as ‘Poor History’? Historiography, Rhetoric, and the Controversies about Solon in the Fourth Century - Correa, Denis (Histos, 2019)
This article examines the kind of historiographical thought that the Aristotelian Athenaion Politeia reveals in its use of sources, especially in chapters 2–17, which deal with Solon’s political activity. It confronts the scholarly view of the Athenaion Politeia as poor history and argues that its historical reasoning employs the same kind of rhetorical argumentation that would have been acceptable in the intellectual context of fourth-century Greek historiography.